Comparison of Slovenian Traditional Plum Materials with Genetic Resources from the Slovenian Plant Gene Bank - Ternjak, Tina (Agricultura Scientia, 2025)
The Slovenian Plant Gene Bank (SPGB) of the Faculty of Agriculture and Life Sciences houses approximately 250 accessions of stone fruit, with most of the material belonging to the species Prunus domestica L. and Prunus cerasifera Ehrh. The main objectives of this study using a set of 11 SSR primers were: 1. to determine the genetic structure of the traditional Slovenian in situ plum material in comparison to the ex situ the SPGB collection; 2. to identify unique material among the in situ collected accessions; 3. to gain insight into the genetic relationship between the two studied species. The genetic structure of 60 plum samples was analyzed using Principal Coordinate Analysis (PCoA) and Bayesian model-based analysis. PCoA separated the P. cerasifera and P. domestic accessions, while Bayesian model-based analysis revealed that many accessions of P. domestica and P. cerasifera shared a common ancestral history. The ex situ material showed greater genetic diversity as it was distributed over more populations than the in situ material. Promising in situ genotypes, especially from the Prekmurje and Lower Styria, were identified as valuable additions to enrich the existing collection.
Keywords: plum; Prunus domestica L.; Prunus cerasifera Ehrh.; SSR markers; genetic structure